PENERAPAN FRAMEWORK MAN IN THE MIDDLE MENGGUNAKAN LINUX PADA LEMBAGA PENYIARAN PUBLIK RRI BENGKULU - Anggiat Faisal Panjaitan; Reno Supardi; Abdussalam Al Akbar (JTIS: Journal of Technopreneurship and Information System, 2021)
AbstrackThe development of very advanced technology has resulted in the level of need for network security being very important.  Conditions like this require network technicians to provide security for internet use by finding out many things that make them understand how network security works, information theft can be done in several ways, one of which is by monitoring the network using software and recording information in clear text.  The purpose of this study is to understand how the MITM (Man In The Middle) Framework works. The method used is the Network Development Life Cycle (NDLC) method, a cycle of network design stages that can guide a network design, which depends on the size of the project to be implemented and the objectives of the project.  Wireless security testing using MITM which is used to find information and security analysis using the arp spoofing technique method, which will be described in the MITM Framework application.  Packet sniffing is a process for capturing packets passing through a computer network. Based on the analysis and attack experiments carried out, it still needs improvement, this is with the airodamp-ng application detecting nearby WiFi and packet snoofing attacks can display website address, username and password information using the MITM Framework application. Keywords: Framework, MITM, wifi,  internet